Corporate Environmental Responsibility, Growth and Life Cycle of Cash Holding - Andi Aditya Hardinto; Juniati Gunawan; Idrianita Anis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This writing examines the effect of environmental responsibility, growth and company life cycle on cash holding – In this study, the use of secondary data in the form of annual report of manufacturing companies obtained through the official website of the Indonesia Stock Exchange (www.idx.co.id), a sustainability report that can be obtained through the company's website and GRI-Database during the 2018-2020 period with a total sample of 195 samples. The results of multiple linear regression analysis can be concluded, that environmental responsibility affect cash holding negatively, growth has a positive influence direction on cash holding and the Company's life cycle in the stagnant stage has a positive effect on cash holding.